Conceptual Understanding and Reasoning of Students with Dyscalculia: A Literature Review - Salisa, Resminati Dinda; Rahaya, Wardani (LPPM Universitas Terbuka, 2023)
Dyscalculia is a specific learning condition that affects one’s understanding and manipulation of numerical concepts. Conceptual understanding is one of the components of mathematics proficiency that can be developed through reasoning skills. However, neither the conceptual understanding nor the reasoning abilities of students with dyscalculia have been thoroughly described. The objective of this systematic review of the relevant scientific literature is to identify and analyse existing evidence regarding the conceptual understanding and reasoning skills of students with dyscalculia by using the following procedures: (1) developing a research question; (2) selection criteria; (3) developing the search strategy; (4) study selection process; (5) appraising the quality of studies; and (6) synthesis result. Twenty articles were selected and analysed in total. It was discovered that students with dyscalculia lacked conceptual understanding and reasoning skills, which could present them with a variety of difficulties, such as processing mathematical facts and further developing their mathematical skills.